(untitled) (Palimpsesto, 2018)
The main objective of this article, centered on the analysis of the novel El día que me quieras, written by Osvaldo Rodríguez, consists in unveiling and evaluating the strategic function of the political and cultural memory of the Spanish Civil War. In fact, this conflict appears as the imaginary articulator of the process of political subjectivation proper to Chilean society in the sixties of the last century, until the triumph of Popular Unity. It is confronted, then, the historical and conceptual relationship between Chile’s socialist experience in the general framework of the revolutionary power of modernity from the expression of the popular political commitment of the youth of Valparaiso in the 1960s, signed by the communist significant.